Analysis of factors related with farmers”™ benefiting from forage crops production support: Evidence from a survey for the Central Anatolia Region of Turkey - Mac, Hakan; Yilmaz, Hasan (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2016)
This study aims to determine the factors affecting the farmers”™ benefiting from forage crops production support in the Eregli district of Konya province in the Central Anatolia region of Turkey. Data were obtained by a questionnaire administered to 69 forage crops farms selected by stratified random sampling. Chi-square test was used to analyze the existence of association between “benefiting or not” and each of the socio-economic variables. The result of the analyses showed that education level, farming experience, size of total farm land, size of forage crops cultivation area, size of field crop cultivation area, membership of a cooperative, state of dealing with non-agricultural activity and certificate seed usage variables were significantly related with farmers”™ benefiting from forage crops production support. Considering all these results, it could be said that, increasing forage crops production was a major goal for developing sustainable livestock sector in Turkey. For this reason, cultivation area of forage crops should be increased and priority should be given to forage crops within the crop rotation system particularly in fallow areas. Present incentive support for cultivation of forage crops should be continued and increased. In addition to farmers”™ problems and requests into consideration should be given priority to policy applications in forage crops production.